Macroalgal–bacterial interactions: Role of dimethylsulfoniopropionate in microbial gardening by Ulva (Chlorophyta). Issue 8 (7th February 2018) - Kessler, Ralf W.; Weiss, Anne; Kuegler, Stefan; Hermes, Cornelia; Wichard, Thomas
Abstract: The marine macroalga Ulva mutabilis (Chlorophyta) develops into callus‐like colonies consisting of undifferentiated cells and abnormal cell walls under axenic conditions. Ulva mutabilis is routinely cultured with two bacteria, the Roseovarius sp. MS2 strain and the Maribacter sp. MS6 strain, which release morphogenetic compounds and ensure proper algal morphogenesis. Using this tripartite community as an emerging model system, we tested the hypothesis that the bacterial–algal interactions evolved as a result of mutually taking advantage of signals in the environment. Our study aimed to determine whether cross‐kingdom crosstalk is mediated by the attraction of bacteria through algal chemotactic signals. Roseovarius sp. MS2 senses the known osmolyte dimethylsulfoniopropionate (DMSP) released by Ulva into the growth medium. Roseovarius sp. is attracted by DMSP and takes it up rapidly such that DMSP can only be determined in axenic growth media. As DMSP did not promote bacterial growth under the tested conditions, Roseovarius benefited solely from glycerol as the carbon source provided by Ulva . Roseovarius quickly catabolized DMSP into methanethiol (MeSH) and dimethylsulphide (DMS). We conclude that many bacteria can use DMSP as a reliable signal indicating a food source and promote the subsequent development and morphogenesis in Ulva .